THE INFLUENCE OF COCOA PRICE VOLATILITY (Theobroma cacao L.) TO COCOA EXPORTS IN INDONESIA - Dessanty Fauziah Widayat; Ratya Anindita; Putri Budi Setyowati (Agricultural Socio-Economics Journal, 2019)
Production or supply of domestic cocoa cannot fulfil the demand for cocoa in domestic and international markets. Furthermore, there were many old cocoa plants, damaged, unproductive and attacked by pests and diseases with mild, medium to serious condition in 2008. Cocoa production still depends on the weather, which can result in the undetermined change of cocoa price. This problem will fluctuate and if this happens continuously then volatility of cocoa price tends to be high. This research uses historical volatility method to measure the price volatility of cocoa in 2007 until 2016. It indicates that volatility of Indonesia cocoa price is high. In order to determine whether or not volatility of cocoa price affects Indonesian cocoa’s exports, stationary tests, cointegration tests and Error Correction Model (ECM) are used. Its result shows that cocoa price volatility and cocoa exports variable are cointegrated and they have negative relation both in the short term and long term. In addition, the variables of volatility cocoa and cocoa exports in Indonesia are out of equilibrium.